Back after this ebook A novel. - Holmes, Linda (2025)
From the New York Times bestselling author of Evvie Drake Starts Over and Flying Solo , a podcast producer agrees to host a new series about modern dating—but will the show jeopardize her chance at finding real love? “Romantic, smart, and exactly the book we all need right now. I adored this.”—Annabel Monaghan, author of Nora Goes Off Script “You’ll sink into this story and never want it to end.”—Elissa Sussman, author of Funny You Should Ask Cecily Foster loves to make podcasts. She fiercely protects her colleagues, dearly adores her friends, and never misses dinner with her sister. But after a disastrous relationship with a colleague who stole her heart and her ideas, she’s put romantic love on hold. When the boss who’s disappointed her again and again finally offers her the chance to host her own show, she wants to be thrilled. But there’s a catch—actually, two catches. First, the show will be about Cecily’s dating life. And second, she has to follow the guidance of influencer and newly minted relationship coach Eliza Cassidy, whose relentlessly upbeat attitude seems ready-made for social media, not real life. Cecily would rather do anything other than put her singledom on display (ugh) or take advice from the internet (UGH). But when her boss hints that doing the show is the only way to protect a friend’s job, she realizes she has no choice. To make matters more complicated, once she’s committed to twenty blind dates of Eliza’s choosing, Cecily finds herself unable to stop thinking about Will, a photographer she helped to rescue a very big and very lovable lost dog. Even though there are sparks between the two, Will’s own path is uncertain, and Eliza’s skeptical comments about Cecily’s decision-making aren’t helping. On the one hand, Will seems great. But on the other hand . . . don’t they all? As Cecily struggles to balance the life she truly desires and the one Eliza wants to create for her, she finds herself at a crossroads. Can Cecily sort through all the advice and find a way to do what she loves without losing herself in the process?